Identification and Partial Characterization of a Novel UDP-N-Acetylenolpyruvoylglucosamine Reductase/UDP-N-Acetylmuramate:l-Alanine Ligase Fusion Enzyme from Verrucomicrobium spinosum DSM 4136T - Naqvi, Kubra F.; Patin, Delphine; Wheatley, Matthew S.; Savka, Michael A.; Dobson, Renwick C. J.; Gan, Han Ming; Barreteau, Hélène; Blanot, Didier; Mengin-Lecreulx, Dominique; Hudson, André O. (Frontiers in Microbiology, 2016)
The enzymes involved in synthesizing the bacterial cell wall are attractive targets for the design of antibacterial compounds, since this pathway is essential for bacteria and is absent in animals, particularly humans. A survey of the genome of a bacterium that belongs to the phylum Verrucomicrobia, the closest free-living relative to bacteria from the Chlamydiales phylum, shows genetic evidence that Verrucomicrobium spinosum possesses a novel fusion open reading frame (ORF) annotated by the locus tag (VspiD_010100018130). The ORF, which is predicted to encode the enzymes UDP-N-acetylenolpyruvoylglucosamine reductase (MurB) and UDP-N-acetylmuramate:L-alanine ligase (MurC) that are involved in the cytoplasmic steps of peptidoglycan biosynthesis, was cloned. In vivo analyses using functional complementation showed that the fusion gene was able to complement E. coli murB and murC temperature sensitive mutants. The purified recombinant fusion enzyme (MurB/CVs) was shown to be endowed with UDP-N-acetylmuramate:L-alanine ligase activity. In vitro analyses demonstrated that the latter enzyme had a pH optimum of 9.0, a magnesium optimum of 10 mM and a temperature optimum of 44-46 oC. Its apparent Km values for ATP, UDP-MurNAc and L-alanine were 470, 90 and 25 µM, respectively. However, all attempts to demonstrate an in vitro UDP-N-acetylenolpyruvoylglucosamine reductase (MurB) activity were unsuccessful. Lastly, Hidden Markov Model-based similarity search and phylogenetic analysis revealed that this fusion enzyme could only be identified in specific lineages within the Verrucomicrobia phylum.